Contribution of microfinance institution to poverty reduction among rural women: A case study of MFI's in Nyamagana District. - Mkali, Grace (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirement for the Degree of the Masters of Business Administration (MBA) of Mzumbe University